Customer Relations Management (CRM) practices in small business, period 2010 to 2019 - Arango Aramburu, Johana Elizabeth (2021)
The purpose of this study is to determine the level of interest in research related to Customer Relationship Management (CRM) practices in small companies from 2010 to 2019, in the main marketing scientific journals. The methodology used consists of the literature review on CRM in a sample of 151 articles published in the last decade of the main marketing journals, located in the first quartile Q1, according to Scimago Journal Rank. The results show that out of 125 empirical articles devoted to Customer Relationship Management (CRM), 72 publications obtain information from large companies, followed by 46 articles that simultaneously extract data from small, medium and large companies; and only 7 CRM articles report the reality of small businesses. It is concluded that there is greater interest in developing CRM research directed towards large corporations, compared to small companies.